Os Fundos de Pasto do município de Monte Santo (BA) e a política de desenvolvimento territorial : conflitos e interesses territoriais no campo - Marques, Leônidas de Santana (2013)
In recent years, the debate about Fundos and Fechos de Pasto communities has grown considerably. This can be recognized as a major step forward in the context of academic thought that can insert more intensely in the national agrarian context and structure. It was necessary to analyze some intricacies that pertain to communities daily life, particularly regarding their relationship with the State. In this sense, the objective of this dissertation is to analyze the relationship between the process of struggle and resistance of Fundos de Pasto communities and territorial development policy at Monte Santo city, in Bahia state, Brazil. Along this, the creation of institutional territories ("rural" and "da cidadania" on a national scale, and "de identidade" on a regional scale) is related with the way as today the State behaves as an agent in the capitalist production of geographical space. From the methodological point of view, the approach was based on analytical historical and dialectical materialism and the geographical perspective of the production of space, with territory as central concept. The research was based on a predominantly qualitative analysis, using primary data (interviews and focus groups) and secondary (from government and non-governmental institutions). Fundos de Pasto communities reality in general and specific features of Monte Santo municipality were analyzed in the first few chapters, taken quantitative and historic data of agrarian economy into account, aiming to recognize and to spatialize the various ways in which locally materializes the peasant conflict for land/territory. After this, it was considered the process of internationalization of capital and their reflections about the State, relating to the way in which public policies are designed. Finally, it was more thoroughly analyzed the insertion of Monte Santo municipality and their communities in the context of Território do Sisal and the State s management and planning mechanisms, linking it with the various interests that are stroked and the connection between appearance and essence in building institutional territories. It is acknowledged that the territorial development policy necessarily exists following two basic premises, which are essentially convergent: first, it will never be viable from the democratic and popular State point of view, because it will not be from institutional mechanisms that will have its nature changed; second, the territorial development policy is completely feasible from the point of view that might become the guarantor of capital progress from mechanisms that incorporate social participation as save-conduct.